1995
DOI: 10.1007/bf00808409
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin (SA) accumulation by bronchogenic tumours: a tracer technique may help with patient selection for SA-delivered chemotherapy

Abstract: Systemic toxicity and inadequate tumour uptake of chemotherapeutic agents limit effective therapy of disseminated malignant disease. We seek to use macromolecules for improved delivery of therapeutic agents to tumours, and hope to use radiotracer procedures to identify those malignancies able to accumulate the transport molecule. A literature search identified in vitro and animal experimental data which indicated that serum albumin is taken up in malignancies. Selected cytostatic drugs can be bound to albumin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The EPR effect is attributed to pathological alterations of tumor vasculature such as high density and increased permeability of the vessels and to an ineffective lymphatic drainage of tumor interstitium. Macromolecules could therefore be successfully used as carriers for the targeting of anticancer drugs to tumors (2,3). Moreover, the tumoritropic effect of macromolecules can be exploited for the delivery of covalently attached contrast agents to tumors for cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The EPR effect is attributed to pathological alterations of tumor vasculature such as high density and increased permeability of the vessels and to an ineffective lymphatic drainage of tumor interstitium. Macromolecules could therefore be successfully used as carriers for the targeting of anticancer drugs to tumors (2,3). Moreover, the tumoritropic effect of macromolecules can be exploited for the delivery of covalently attached contrast agents to tumors for cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 We have introduced a new albumin-MTX conjugate ( Fig. 14,15 Consequently, HSA was deemed feasible as a drug carrier and conjugates with MTX as chemotherapeutic agent were prepared. 9,10 The rationale for the design of this drug is based on the fact that plasma proteins constitute the major transportable nitrogen reserve in vertebrates.…”
mentioning
confidence: 99%
“…13 Radiopharmacokinetic studies in laboratory animals and humans using radiolabeled HSA have revealed enhanced uptake and degradation of albumin by solid tumors. 14,15 Consequently, HSA was deemed feasible as a drug carrier and conjugates with MTX as chemotherapeutic agent were prepared. 16 -20 Interestingly, drug conjugates bearing multiple MTX molecules per albumin were rapidly cleared from circulation and predominately trapped by the monocyte-macrophage system of the liver.…”
mentioning
confidence: 99%